Survei tingkat kebugaran jasmani atlet remaja akademi basket rookie - Jatmiko, Agung Basori; Syaukani, Agam Akhmad (Universitas Hamzanwadi, 2023)
Physical fitness also has a strong relationship with talent and health. Achievement in athletics correlates with other types of success, including other criteria such as physical fitness. This study aims to determine the level of physical fitness of young athletes at the Klaten rookie basketball academy. This descriptive research uses a survey approach. 20 basketball players. Tests and measurements are used in the data collection method. Indonesian Physical Fitness Test (TKJI) for the 16-19 year age group. Descriptive statistical analysis research using percentages is a method of data analysis. The results showed that young athletes had a moderate level of physical fitness, with 0 people (0%) having a poor level of physical fitness, 1 person (5%) having a low level of physical fitness, 9 people (45%) having a moderate level of physical fitness , and 0 people (0%) have a very good level of physical fitness. The conclusion is that most of the young athletes have a level of physical fitness which is included in the very good group, with 10 participants (or 50%) having the highest frequency in this field